Digitalizing Arabic Literary Learning: Content Material Mapping and Presentation Strategies on The Instagram Account @puisi_arab - Ferawati Ferawati; A. Syahid Robbani; Erissa Adittya Pramaishella; Ahmad Aziz Ismail (PT. Global Research Collaboration, 2026)
The rapid development of social media, particularly Instagram, has created new spaces for the practice of teaching and learning Arabic language and literature beyond formal educational institutions. Previous studies have extensively examined Arabic language educational content on Instagram; however, research focusing specifically on Arabic literary content remains limited. Therefore, this study aims to map the content materials and analyze the strategies for presenting Arabic literary learning content on the Instagram account @puisi_arab. It seeks to address this research gap while encouraging scholars and practitioners of Arabic literature to contribute to enriching the presentation of literary content through Instagram. The analysis focuses on learning materials presented and content presentation strategies. This study adopts a qualitative content analysis approach, with data derived from 35 posts on the @puisi_arab account selected through systematic sampling techniques. The findings indicate that the account presents a wide range of Arabic literary learning materials, including classical poetry, modern poetry, literary aphorisms (ḥikam), qaṣīdah, poetry, prose, and the history of Arabic literature. The content presentation strategy utilizes a combination of literary texts, illustrative visuals, background music, and interpretive narration in captions, with a dominant use of the single-image format that displays excerpts of poetry and prose accompanied by explanatory captions. These findings suggest that social media can function as an alternative space for the dissemination and appreciation of Arabic literature in the digital era, while also offering opportunities for the development of microlearning-based literary instruction models.